Towards Improved Farm Structures and Rural Land Market Functioning : Policy Options Based on Lessons from European Experience - van Holst, Frank (World Bank, Washington, DC, 2018)
Most transition countries in Central and Eastern Europe face enormous challenges in developing a viable land structure. Due to restitution processes and socially engaged policies of privatization, wide spread land fragmentation is present. The situation in Armenia is comparable with many other countries in the region. Privatization was mainly done in the 1990s but continues until now as state and public land still represent a relatively large share of agricultural land. Figures of Armenia over the last 20 years illustrate minimal change in average farm and plot size. This outline is based on review and analysis of available data and a visit to Armenia in June 2017. It aims to contribute to selecting the policy options and setting the preconditions in Armenia needed to get a well-functioning rural land market to enlarge farms and to reduce fragmentation. As shown in this report, experience in the region is still limited which made it necessary and relevant to refer to experience in Western European countries. Options are not limited to land consolidation but include improved management of state land, land banking, agricultural lease regulation and some other supporting measures. The analysis conducted for this report draws on data collected from the Agricultural Census data of 2014 and data from the Real property cadastre. Qualitative data are based on several reports, presentations and interviews with experts and policy makers listed in the annex. Although further analysis is needed, it is clear that the current situation provides a serious risk for the agricultural sector which jeopardises the impact of any support to the sector. While Western European countries could organically adapt and support the sector to changing market conditions since the 1950s, the situation in Armenia (and other countries in the region) requires a set of measures which is unprecedented in its scale and intensity to speed up this process.